The Effectiveness of Drama as an Instructional Approach for the Development of Second Language Oral Fluency, Comprehensibility, and Accentedness. Issue 1 (5th February 2016) - Galante, Angelica; Thomson, Ron I.
Abstract : Although the development of second language (L2) oral fluency has been widely investigated over the past several decades, there remains a paucity of research examining language instruction specifically aimed at improving this cognitive skill. In this study, the researchers investigate how instructional techniques adapted from drama can positively impact L2 fluency, comprehensibility, and accentedness—three frequently discussed dimensions of L2 speech. Following a pretest–posttest design, the researchers obtained speech samples from 24 adolescent Brazilian EFL learners before and after their participation in a 4‐month drama‐based English language program. The development of oral skills by this group was compared with that of a parallel group of learners who received 4 months of instruction in a traditional communicative EFL classroom. Thirty untrained Canadian native English speaker raters evaluated randomized recorded L2 speech samples and provided impressionistic scalar judgments of fluency, comprehensibility, and accentedness. Results indicate that drama‐based instruction can lead to significantly larger gains in L2 English oral fluency relative to more traditional communicative EFL instruction; comprehensibility scores also appear to be impacted, but with a much smaller effect; accentedness scores do not seem to benefit from one type of instruction over the other. The authors discuss implications for teaching practice. Abstract : Video abstract link:https://www.youtube.com/watch?v=hYUUc5ZMiyo